El principio de Interculturalidad y el Aprendizaje colaborativo en los estudiantes de la Carrera de Peda ogía de la Historia y las Ciencias Sociales de la UNACH. - Vite Vera, Abrahan Nexar (2024)
This research was conducted at the National University of Chimborazo with students from the History and Social Sciences Pedagogy Career. Within this educational context, various ethnicities were found, and the most predominant were indigenous and mestizo. If we talk about something more specific concerning the students ofthe indigenous ethnic group, a bit ofinsecurity and devaluation oftheir own identity could be evident. They do not have an interest in interacting with mestizo classmates, and there is the presence of students who do not wear their traditional clothing.